Management of recurrent aqueous misdirection by anterior segment surgeon after failed pars plana posterior vitrectomy - Vanita Pathak Ray; Varun Malhotra (Indian Journal of Ophthalmology, 2019)
Aqueous misdirection (AM) is a dreaded complication, but fortunately quite rare. It usually occurs after intervention for angle closure glaucoma. When pharmacotherapy and/or laser interventions are unsuccessful, then the surgical management hitherto most commonly undertaken is pars plana posterior vitrectomy. We describe the management of recurrent AM via the anterior route, when it occurred following relapse as pars plana posterior vitrectomy failed to result in long-term normalization of anterior chamber and intraocular pressure. Anterior vitrector with anterior vitrectomy settings was used by a glaucoma specialist to carry out the procedure.